Odvádění výroby ve vybraném podniku - Eibelová, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Bakalářská práce se zaměřuje na snížení administrativy a chybovosti při ručním odvádění výroby ve slévárně. Analýza mapuje aktuální stav procesů v provozu a znázorňuje tak jeho chod. Práce přináší návrh na vyřešení daného problému zavedením MES systému, který se nainstaluje do slévárny.

The bachelor thesis focuses on the reduction of administrative and error rate in manual removal of the production in the foundry. The analysis maps the current state of the processes in the operation and shows how it works. This thesis presents a proposal to solve the problem by introducing the MES system, which is installed in the foundry.
Dropping Production in the Company
Keywords: proces; modelování procesů; odlévání; výrobní informační systém (MES); process; modeling of processes; casting; Manufacturing Execution System